2010
DOI: 10.3324/haematol.2010.026658
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic follow-up by karyotyping and fluorescence in situ hybridization: implications for monitoring patients with myelodysplastic syndrome and deletion 5q treated with lenalidomide

Abstract: In patients with low and intermediate risk myelodysplastic syndrome and deletion 5q (del(5q)) treated with lenalidomide, monitoring of cytogenetic response is mandatory, since patients without cytogenetic response have a significantly increased risk of progression. Therefore, we have reviewed cytogenetic data of 302 patients. Patients were analyzed by karyotyping and fluorescence in situ hybridization. In 85 patients, del(5q) was only detected by karyotyping. In 8 patients undergoing karyotypic evolution, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Controversy exists regarding whether iFISH is necessary at the initial diagnosis of MDS and/or during followup. [4][5][6][7][8][9][10][11] Some studies suggest that iFISH can be performed only in cases of mitotic failure or abnormal karyotype. 5,7,8,11,12 Others have reported discrepancies between iFISH and Gbanding in MDS with monosomy 7 and observed that FISH can more sensitively reflect disease progression.…”
mentioning
confidence: 99%
“…Controversy exists regarding whether iFISH is necessary at the initial diagnosis of MDS and/or during followup. [4][5][6][7][8][9][10][11] Some studies suggest that iFISH can be performed only in cases of mitotic failure or abnormal karyotype. 5,7,8,11,12 Others have reported discrepancies between iFISH and Gbanding in MDS with monosomy 7 and observed that FISH can more sensitively reflect disease progression.…”
mentioning
confidence: 99%
“…Aberrations in cell cycle control may promote accumulation of additional mutations and influence clonal progression to AML (26). In patients with MDSs, CDC25C is part of the commonly deleted region on chromosome 5q (27,28). Furthermore, alternative splicing of CDC25C has been observed in bone marrow samples from patients with MDS (29) and downstream of the SRSF2-P95 mutant (30).…”
Section: Discussionmentioning
confidence: 99%
“…17,23 At diagnosis there was minimal discordance between standard karyotyping and FISH (4%). But surprisingly, at 18 months post-diagnosis, 84 of 267 patients (31%) showed del(5q) by karyotyping, but not by FISH.…”
Section: Importance Of the Methods Of Genetic Monitoringmentioning
confidence: 99%